Management of Urologic Cancer 2017
DOI: 10.1002/9781118868126.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance for Low‐Risk Prostate Cancer

Abstract: Active surveillance for localized prostate cancer entails initial expectant management rather than immediate therapy, with "curative-intent" treatment deferred until there is evidence that the patient is at increased risk for disease progression. This is a response to the clearly documented risks of over diagnosis and overtreatment of low-risk prostate cancer, which in most cases poses little or no threat to the patient. It is based upon the prolonged natural history of prostate cancer and is an attempt to bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Active surveillance (AS) represents an increasingly used option that aims to delay or avoid active treatment in selected patients with localised prostate cancer [1][2][3][4]. The oncological safety of this approach strongly depends on the adoption of strict selection criteria to identify eligible patients [5]. Although pathological findings at radical prostatectomy (RP) represent surrogate endpoints when developing selection approaches for AS candidates, several criteria that would allow for the reliable identification of insignificant prostate cancer that would pose little threat to patients, even if left untreated, have been proposed [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Active surveillance (AS) represents an increasingly used option that aims to delay or avoid active treatment in selected patients with localised prostate cancer [1][2][3][4]. The oncological safety of this approach strongly depends on the adoption of strict selection criteria to identify eligible patients [5]. Although pathological findings at radical prostatectomy (RP) represent surrogate endpoints when developing selection approaches for AS candidates, several criteria that would allow for the reliable identification of insignificant prostate cancer that would pose little threat to patients, even if left untreated, have been proposed [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the cancer-specific mortality is probably 3% or less after 10-15 years, if AS is the primary choice. 6 However, there are four main reasons to assume that patients' risk estimates will be biased. 7 (i) Because RP is still framed as the "default" 8 in clinical practice, it is likely that patients estimate the cancerspecific mortality risk for AS significantly higher than that for RP.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that the mortality rate of those managed with AS is consistent with that of patients who had an initial definitive intervention over a 15‐year period. 11 , 12 , 13 As a result, there has been a greater focus on identifying and incorporating reliable prognostic indicators in patients diagnosed with low‐grade disease.…”
Section: Introductionmentioning
confidence: 99%